Vegetarian dietary patterns and cardiovascular risk factors and disease prevention: An umbrella review of systematic reviews - Matthew J. Landry; Katelyn E. Senkus; A Reed Mangels; Nanci S. Guest; Roman Pawlak; Sudha Raj; Deepa Handu; Mary Rozga (American Journal of Preventive Cardiology)
Background: Diet significantly influences the risk of developing cardiovascular disease (CVD), the leading cause of death in the United States. As vegetarian dietary patterns are increasingly being included within clinical practice guidelines, there is a need to review the most recent evidence regarding if and how these dietary patterns mitigate CVD risk. Objective: This umbrella review of systematic reviews compared the relationships between vegetarian, vegan and non-vegetarian dietary patterns and CVD health outcomes and risk factors among presumably healthy adults (≥18 years) in the general population. Methods: MEDLINE, CINAHL, Cochrane Databases of Systematic Reviews, Food Science Source and SportsDiscus databases were searched for systematic reviews (SRs) published from 2018 until March 2024. Eligible SRs and meta-analyses examined relationships between vegetarian or vegan diets and CVD risk factors and disease outcomes compared to non-vegetarian diets. SRs were screened in duplicate, and SR quality was assessed with AMSTAR2. The overall certainty of evidence (COE) was evaluated using the Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) method. Results: There were 758 articles identified in the databases’ search and 21 SRs met inclusion criteria. SRs targeting the general population had primarily observational evidence. Vegetarian, including vegan, dietary patterns were associated with reduced risk for CVD incidence [Relative Risk: 0.85 (0.79, 0.92)] and CVD mortality [Hazard Ratio: 0.92 (0.85, 0.99)] compared to non-vegetarian diets. Vegan dietary patterns were associated with reductions in CVD risk factors including blood pressure [systolic mean difference (95 % CI): -2.56 mmHg (-4.66, -0.445)], low-density lipoprotein cholesterol [-0.49 mmol/l (-0.62, -0.36)], and body mass index [-1.72 kg/m2 (-2.30, -1.16)] compared to non-vegetarian dietary patterns, as well as c-reactive protein concentrations in a novel meta-analysis [-0.55 mg/l (-1.07, -0.03)]. Conclusion: Practitioners can consider recommending vegetarian dietary patterns to reduce cardiometabolic risk factors and risk of CVD incidence and mortality.